2015
DOI: 10.14257/ijseia.2015.9.12.32
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Anxiety and Dyadic Adjustment on Maternal–Fetal Attachment in High-Risk Pregnant Women

Abstract: This study attempted using a descriptive survey to elucidate the influence of anxiety and dyadic adjustment on maternal-fetal attachment in high-risk pregnant women. Methods: The data used in this study were collected from March 3 rd , 2015, to March 30 th , 2015, and the participants were 118 pregnant women including those undergoing prenatal tests and those admitted to a delivery room in the obstetrics outpatient center of 3 university hospitals located in B, D, and Y after diagnosis with high-risk pregnancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
1
2
1
1
Order By: Relevance
“…Other influencing factors were anxiety and family support. This result is similar to the findings of a previous study in high-risk pregnant women [2] that reported that anxiety and marital adaptation influenced maternal-fetal attachment. Another study of women who experienced miscarriage noted that spousal support was a factor associated with maternal-fetal attachment [12].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Other influencing factors were anxiety and family support. This result is similar to the findings of a previous study in high-risk pregnant women [2] that reported that anxiety and marital adaptation influenced maternal-fetal attachment. Another study of women who experienced miscarriage noted that spousal support was a factor associated with maternal-fetal attachment [12].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the average anxiety score was 43.57 out of a total of 80. This is higher than previously reported scores of 39.02 points in high-risk pregnancies [2] and 39.3 points in normal pregnancies [9] using the same tool. As state anxiety ranged from 21 to 79 points, reflecting significant variation among individuals, nursing interventions for pregnant women in the MFICU should carefully note differences in individual characteristics and the degree of anxiety.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…모아애착은 출산 전 모아관계의 출발점으로 임부와 태아가 정서적인 유대감을 가지는 행위이다[ 7 ]. 고위험 임부는 정상 임부에 비해 임신 기간 동안 태아와 자신의 안녕을 예측하기 힘든 상태이므로 걱정·불안과 같은 부정적인 정서를 더 많이 경험하게 되며[ 8 ], 이로 인해 모아애착 형성에 어려움을 겪는 것으로 나타났다[ 9 ]. 임신 중 모아애착의 형성은 출산 후 자녀와의 관계에 영향을 미치며[ 10 ], 모체의 모아애착이 낮은 경우 영아는 까다로운 성격을 가지는 경우가 많고, 수면과 적응 행동 발달에도 문제가 발생한다고 보고한 체계적 문헌고찰[ 11 ]을 고려하면 자녀의 심리적, 신체적인 발달에도 영향을 미치는 요소가 될 수 있으므로 그 중요성이 매우 높다.…”
Section: Introductionunclassified